Preparation and Findings in Diagnostic and Therapeutic Flexible Fiberoptic Bronchoscopy Procedures in Patients with COVID-19 - Irandi Putra Pratomo; Hario Baskoro; Dicky Soehardiman; Prasenohadi Prasenohadi; Tutug Kinasih; Ahmad Fauzi; Ike Maretta; Nachita Putri; Kentaro Tokumo (Jurnal Respirasi, 2023)
The coronavirus disease 2019 (COVID-19), which has raised concerns about infection control for every clinical procedure, including flexible fiberoptic bronchoscopy (FFB), has drawn the attention of clinicians across the globe. A pulmonologist frequently conducts this procedure to diagnose and treat pulmonary diseases like COVID-19. This procedure involves direct airway observation and generates aerosol from the patient. However, it is considered a double-edged sword, as the risk of infection and instrument contamination always haunts its clinical benefit to the patients and the operators. Therefore, a guideline for preparing and indicating FFB in COVID-19 must be addressed appropriately by emphasizing the importance of infection prevention and control. Fortunately, several recommendations and findings have emerged over the past three years, which should support safe FFB procedures for its operators with controlled infection. This study summarizes the indication, objective, contraindication, risk, preparation, and findings in diagnostic and therapeutic FFB patients with COVID-19.